Patients' choice preferences for specialist outpatient online consultations: A discrete choice experiment - Wu, Mengqiu; Li, Yuhan; Ma, Chengyu (Frontiers in Public Health, 2023)
Background Internet hospitals are multiplying with solid support from the Chinese government. In internet hospitals, specialist outpatient online consultations (SOOC) are the primary services. However, the acceptance and utilization rates of this service are still low. Thus, the study of patients' choice preferences for SOOC is needed. Objective To analyze the choice preference of patients' SOOC via a discrete choice experiment, understand the influence of each factor and promote the development of internet hospitals. Methods Via a discrete selection experiment, a total of 162 patients from two general hospitals and three specialized hospitals in Beijing were selected for the questionnaire survey. The choice preferences were analyzed by conditional logit regression. Results From high to low, patients' willingness to pay (WTP) for the attributes of SOOC is as follows: doctors' recommendation rate (βhighly recommend = 0.999), the convenience of applying SOOC services (βConvenient = 0.760), the increasing ratio of medical insurance payment for online services compared to offline (βIncrease by 10% = 0.545), and the disease's severity (βsevere = −3.024). The results of the subgroup analysis showed differences in patient choice preference by age, whether the patients had chronic diseases, income, and medical insurance types. Conclusion Both price and nonprice attributes influence the choice preference of SOOC for patients. Among them, patients are more inclined to choose SOOC when doctors highly recommend it, when it is convenient to apply, when medical insurance increases by 10%, and when disease severity is mild. The current findings show the government and medical institutions formulate auxiliary policies and welfare strategies by clarifying core attributes and adjusting the levels of different attributes to improve patients' acceptance of SOOC. The utility of SOOC and the further development of internet hospitals are radically promoted.